Phase transition induced by synchroshear in Al-Zn-Mg-Cu alloy. (15th April 2022) - Xiang, Kaiyun; Ding, Lipeng; Jia, Zhihong; Yang, Xiaofang; Liu, Qing; Hao, Zhang
Abstract: Phase transition of the η-MgZn2 Laves phase from C14 to C15 structure in peak aged Al-Zn-Mg-Cu alloy were studied by atomic resolution high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) and density functional theory (DFT) calculations. The formation of a well ordered C15 structural MgZn2 as independent precipitate is for the first time observed in Al-Zn-Mg-Cu alloy. The C15 structure is confirmed to be transformed from the C14 by the activation of synchroshear in every other glide plane, which involves the shear induced by two Schockley partial dislocations in the triple-layer of the Laves phase. Besides, the twin-like structure and five-fold symmetry twin are formed for composing C15 structure due to multiple synchroshear. These results expand the structural understanding of the η-MgZn2 precipitates in Al-Zn-Mg-Cu alloy.